Functional role of voltage gated Ca2+ channels in heart automaticity - Mesirca, Pietro; Torrente, Angelo G.; Mangoni, Matteo E. (Frontiers in Physiology, 2015)
Pacemaker activity of automatic cardiac myocytes controls the heartbeat in everyday life. Cardiac automaticity is under the control of several neurotransmitters and hormones and is constantly regulated by the autonomic nervous system to match the physiological needs of the organism. Several classes of ion channels and proteins involved in intracellular Ca2+ dynamics contribute to pacemaker activity. The functional role of voltage-gated calcium channels (VGCCs) in heart automaticity and impulse conduction has been matter of debate for 30 years. However, growing evidence shows that VGCCs are important regulators of the pacemaker mechanisms and play also a major role in atrio-ventricular impulse conduction. Incidentally, studies performed in genetically modified mice lacking L-type Cav1.3 (Cav1.3-/-) or T-type Cav3.1 (Cav3.1-/-) channels show that genetic inactivation of these channels strongly impacts pacemaking. In cardiac pacemaker cells, VGCCs activate at negative voltages at the beginning of the diastolic depolarization and importantly contribute to this phase by supplying inward current. Loss-of-function of these channels also impairs atrio-ventricular conduction. Furthermore, inactivation of Cav1.3 channels promotes also atrial fibrillation and flutter in knockout mice suggesting that these channels can play a role in stabilizing atrial rhythm. Genomic analysis demonstrated that Cav1.3 and Cav3.1 channels are widely expressed in pacemaker tissue of mice, rabbits and humans. Importantly, human diseases of pacemaker activity such as congenital bradycardia and heart block have been attributed to loss-of-function of Cav1.3 and Cav3.1 channels. In this article, we will review the current knowledge on the role of VGCCs in the generation and regulation of heart rate and rhythm. We will discuss also how loss of Ca2+ entry through VGCCs could influence intracellular Ca2+ handling and promote atrial arrhythmias.